2005
DOI: 10.1111/j.1399-3054.2005.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water deficit on the activity of nitrate reductase and content of sugars, nitrate and free amino acids in the leaves and roots of sunflower and white lupin plants growing under two nutrient supply regimes

Abstract: The effects of a two weeks soil drying period on the activity of nitrate reductase (NR; EC 1.6.6.6) were studied on Helianthus annuus L. and non-nodulated Lupinus albus L. plants, growing under two nutrient supply regimes. NR activity was assessed in leaf and root extracts, by measuring the activity of the unphosphorylated active form (NR act ), the maximal extractable activity (NR max ) and the activation state. To get insight into potential signalling compounds, nitrate, amino acids and soluble sugars concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 40 publications
(87 reference statements)
3
22
0
4
Order By: Relevance
“…An increase in cellular osmolytes under stress conditions has been observed by other authors as well (Carillo et al, 2005;Sharma and Dubey, 2005), and these solutes were supposed to play the role of enzyme protectants. Sugars were shown to act as major osmotic solutes in a number of plant species subjected to dehydration (Irigoyen et al, 1992;Kameli and Lösel, 1995;Bajji et al, 2000;Correia et al, 2005). In the present study, reducing sugars showed a significant increase in response to water stress (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…An increase in cellular osmolytes under stress conditions has been observed by other authors as well (Carillo et al, 2005;Sharma and Dubey, 2005), and these solutes were supposed to play the role of enzyme protectants. Sugars were shown to act as major osmotic solutes in a number of plant species subjected to dehydration (Irigoyen et al, 1992;Kameli and Lösel, 1995;Bajji et al, 2000;Correia et al, 2005). In the present study, reducing sugars showed a significant increase in response to water stress (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Nitrate reductase (NR) is the first and rate-limiting enzyme in the nitrate-assimilation pathway (Lillo et al, 1996). Its activity was shown to decline in water-stressed leaves in a wide range of plant species (Bandurska, 1993;Flores et al, 2000;Correia et al, 2005). The regulation of this particular enzyme is related to several internal and external factors (Vincentz et al, 1993;Lillo et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also estimated the activity of NR since it is the ratelimiting enzyme of nitrogen assimilation and that the maximal foliar extractable NR activity has been found to decrease in situations of water deprivation (Larsson et al 1989;Correia et al 2005), and the decline was correlated with low photosynthetic activity (Baki et al 2000) rather than to water stress itself. The NR activity under drought stress was also modified via changes (i.e., decrease) in NR transcript levels or through phosphorylation-dependent inactivation and proteolytic degradation (Lejay et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this, NR and GS activities also decreased under water deficit, salinity and in combination, but overall, tolerant genotypes exhibited higher GS and NR activities. A number of studies have reported decreased NR activity in response to water stress (Foyer et al, 1998;Correia et al, 2005) and salinity (Wang et al, 2007;Carillo et al, 2008). Salt was observed to inhibit nitrate transport to the leaf mainly because of nitrate ⁄ chloride competition, consequently affecting NR activity (Rao & Gnanam, 1990;Abd-El Baki et al, 2000).…”
Section: Growing Conditions and Genotypic Effects On N Concentration mentioning
confidence: 99%